The Islamic Republic of Iran in Search of its Foreign Policy Identity: Revolutionary Innovation or Continuity? - N. A. Kozhanov; A. S. Bogacheva (Vestnik MGIMO-Universiteta)
Self-perception in the international arena plays a great role in the development of a country's foreign policy strategy. Not all states can answer the question «who are we in relation to others»? In particular, we can describe the past 20 century and the first decades of the 21st century as the time of Tehran's search for its foreign policy identity, which is not finished even today. Despite many discussion, the Iranian political elite has not only failed to find a single definition of its foreign policy selfhood, but has produced several more formulas of its own identity, which often contradict each other, although they coexist. The events of 1979, when the new leadership that came to power in the course of revolutionary upheavals announced the rejection of the traditions of the Shah's Iran and the building of a new "revolutionary" nation with its own special foreign policy identity, had a significant impact on the process of forming the Iranian selfhood. The article analyzes the main trends that exist in the Iranian foreign policy self-perception, in order to confirm the hypothesis that the «revolutionary experiment» did not lead to a break in the continuity in the issue of Iranian self-identification. On the contrary, there is an attempt by the country's leadership to combine Islamic, revolutionary and nationalist principles in determining the role of their country in the international arena, which let us speak about the multi-component foreign policy identity of modern Iran.